3D scanner’s potential as a novel tool for lymphedema measurement in mouse hindlimb models - Dongkyung Seo; Riri Ito; Kosuke Ishikawa; Takahiro Miura; Yuhei Yamamoto; Yasuhito Onodera; Soichiro Nishioka; Yoichi M. Ito; Kanako Fuyama; Taku Maeda (Scientific Reports)
Abstract Lymphedema is characterized by persistent swelling due to impaired lymphatic function and presents significant challenges in both research and clinical settings. Traditional contact-based measurement techniques such as paw thickness and circumferential measurements using calipers or silk thread are useful but limited by observer variability and measurement accuracy. Non-contact methods, including various imaging techniques, offer improvements but often at higher cost and complexity. In this study, we address the need for a more reliable, cost-effective, and non-invasive method for assessing lymphedema in mouse models. Here we show that 3D scanning technology can enhance the measurement of lymphedema in a mouse hindlimb model. Our results indicate that 3D scanners provide more consistent measurements with lower variability compared with conventional methods and without the need for direct contact, which could potentially alter the measurement outcomes. The findings of this study suggest that 3D scanning could replace traditional methods, offering a more standardized and less subjective tool for lymphedema research in the near future. This technology would not only improve upon conventional methods but also extend the capabilities for detailed anatomical analyses in small animal models, which could have implications for other areas of biomedical research.